Gestão de polos municipais do sistema universidade aberta do Brasil: alternativas de financiamento - uma abordagem no estado do Espírito Santo - Bossato, Juliano Pereira (2017)
This research was developed within the scope of the Postgraduate Program in Public Management of the Federal University of Espírito Santo (PPGGP / UFES). It consists of a study whose theme "Municipal Poles Management of the Open University System of Brazil (UAB): financing alternatives - an approach in the state of Espírito Santo" is aligned with "legal aspects in the public sector", is an analysis based on the legislation that regulates the subject and proposes changes. The objective was to identify viable forms of partnerships between the UAB Municipal Poles and private initiative, as an alternative to improve polo infrastructure. For this, it was necessary to know and describe the receptivity of the polo coordinators to these partnerships and to analyze the system that monitors the quality of the infrastructure to identify its weaknesses. In the methodology, the field research was applied through questionnaire, documentary research, in the monitoring system of the UAB poles, in addition to the bibliographic review that based all theoretical reference. It has been found that maintaining the pole infrastructure in ideal conditions is the greatest challenge for coordinators. An example of this occurred between the years 2011 and 2014, when the technical visits culminated in processes of disconnection of some of the Espírito Santo's poles. Because they depend exclusively on the transfer of public resources, the poles become vulnerable and risk being misidentified, since the offer of higher education is not an obligation of the municipality, as provided in article 211, paragraph 3, of the Constitution The current legislation of the UAB is restrictive to the provision of private institution courses at the poles, so the present study has as technical product a legislative amendment, which allows the celebration of publicprivate partnerships, contributing to the capture of resources that can be invested in improvements in infrastructure and in the growth of the EAD modality